1986
DOI: 10.1103/physrevb.33.6744
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic structure of electrons in Li metal: Inelastic synchrotron x-ray scattering results and interpretation beyond the random-phase approximation

Abstract: The dynamic structure factor S(q, tv) of electrons in Li-metal single crystals for q~~ [100], q~~[ 110],and q~~[ 111]with 0.28 a.u. & q & 1.4 a.u. was measured with 1-eV resolution by using inelastic scattering of synchrotron x radiation from DORIS II (Doppel-Ring Speicheranlage). Mainly for q & q, (q, is the plasmon cutoff vector) the fine structure of S(q, co) exhibits a strong dependence on the direction of the momentum transfer q. This crystal-lattice-induced peak structure is connected with minima of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
59
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 53 publications
4
59
2
Order By: Relevance
“…However, recent x-ray measurements [3] and firstprinciples evaluations of the dynamical density response of Al [4,5] and Be [5] have shown that band structure effects cannot be neglected. Unfortunately, calculations of the effects of dynamical correlations for electrons propagating in the actual band structure of Al-or any other metal-are not yet available.…”
mentioning
confidence: 98%
“…However, recent x-ray measurements [3] and firstprinciples evaluations of the dynamical density response of Al [4,5] and Be [5] have shown that band structure effects cannot be neglected. Unfortunately, calculations of the effects of dynamical correlations for electrons propagating in the actual band structure of Al-or any other metal-are not yet available.…”
mentioning
confidence: 98%
“…The incident X-ray beam is inelastically scattered (Compton scattering), a part of the incident photons energy is transferred to the sample through electronic transitions. Under certain experimental conditions, the same XAS features are seen in the Compton scattering profile peak when the transferred energy equals the binding energy of the probed element [36,37]. The use of hard X-ray with a large penetrating power can offer then a good alternative to soft X-ray XAS to probe low energy edges in samples with high absorbing environmental set-up such as confinements in case of radioactive samples, cryostat, high-pressure, high-temperature cells.…”
Section: Additional Possibilities: Inelastic Scattering Experimentsmentioning
confidence: 68%
“…The broken lines give the range of intraband transitions of a free-electron gas in a weak lattice potential. The results are compared with the experimental results of [16]. The calculated dispersion curves of the zone-boundary collective states are shown according to [17] with the parameters for (a) taken from [18] and for (b) from [19].…”
mentioning
confidence: 99%
“…These are excitations that lie in the energy interval that is accessible with the instrument INELAX. The excitations were investigated with an energy resolution of 38 meV [3,5,15] compared to earlier performed experiments [16]. The dispersion curve of the zone-boundary collective states in lithium in [001] direction derived from INELAX data is shown in Figure 8.…”
mentioning
confidence: 99%